Growth Pattern and Condition Factors of Kurisi Fish (Nemipterus nematophorus, Russel 1990) Landed at Lempasing Fishing Port - Nindia Ciandra Niawati; Putriani, Rizha Bery (UNIVERSITAS PGRI MADIUN, 2024)
The kurisi fish (Nemipterus nematophorus) is one of the demersal species caught at PPP Lempasing using purse seine nets. This study aims to obtain information about the growth patterns and condition factors of kurisi fish found in the waters of Teluk Lampung and landed at PPP Lempasing. The methods employed include direct data collection through random sampling of fish, where analysis is conducted to identify the relationship between length and weight as well as the condition factor of the fish. The results indicate that the total catch of kurisi fish reached 350 individuals, with total lengths ranging from 140 to 256 mm, categorized into 9 length classes. The growth pattern of kurisi fish is characterized as negative allometric, with a value of b equal to 2.4405, indicating that the length of the fish grows faster than its weight. The average condition factor of kurisi fish is 0.9763, suggesting that these fish have a flattened body shape.